2023
DOI: 10.3341/kjo.2022.0146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Mitomycin C on the Surgical Outcomes of Ahmed Glaucoma Valve Implantation with Ciliary Sulcus Tube Placement

Abstract: Purpose: To evaluate the effect of intraoperative mitomycin C (MMC) on the surgical outcomes of ciliary sulcus (CS) Ahmed glaucoma valve (AGV) tube placement.Methods: A retrospective review of medical records of 54 consecutive patients who underwent AGV implantation with tube placed in CS was performed. Consecutive cases operated without the use of intraoperative MMC from 2017 to 2019 were compared with consecutive cases operated with MMC from 2019 to 2021. Surgical failure was defined as intraocular pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition to new implants, advancements in bleb surgery have also focused on improving the success of tube surgery and preventing bleb scarring and failure. Several recent studies have evaluated the use of MMC in tube surgery (a topic on which there is no consensus, despite prior studies, see Cantor et al ) [24][25][26]. A prospective, single-center, randomized study of 56 eyes was performed to compare intraoperative injection of mitomycin C (0.15 ml of 0.01%) versus 2-min application of 0.02% soaked sponges during trabeculectomy [27].…”
Section: Advancements In Bleb Surgerymentioning
confidence: 99%
“…In addition to new implants, advancements in bleb surgery have also focused on improving the success of tube surgery and preventing bleb scarring and failure. Several recent studies have evaluated the use of MMC in tube surgery (a topic on which there is no consensus, despite prior studies, see Cantor et al ) [24][25][26]. A prospective, single-center, randomized study of 56 eyes was performed to compare intraoperative injection of mitomycin C (0.15 ml of 0.01%) versus 2-min application of 0.02% soaked sponges during trabeculectomy [27].…”
Section: Advancements In Bleb Surgerymentioning
confidence: 99%
“…Its effectiveness and safety has been demonstrated in some previous reports. [32][33][34][35]66 Ciliary sulcus tube shunt placement was first described by Rumelt and Rehany in 1998. 66 They performed this surgical approach in 3 patients with corneal grafts.…”
Section: Corneal Edema/decompensationmentioning
confidence: 99%
“…To date, the results of ciliary sulcus tube shunt placement was evaluated in various studies and success rates were reported as high as 78.6% to 98.3%. [32][33][34][35] Eslami et al 34 evaluated retrospectively the results of 23 eyes of 23 patients that underwent AGV tube implantation into the ciliary sulcus. In the study the mean follow-up period was 9 months (range 3-24 months) and IOP reduced from 37.9 ± 12.4 mmHg to 16.2 ± 3.6 mmHg at last follow-up visit and the success rate was found as 78.6%.…”
Section: Corneal Edema/decompensationmentioning
confidence: 99%